E-book Publication Dates: Do I Just Not Get It? - Marilyn Geller (Issues in Science and Technology Librarianship)
The author comments on the trend of publishers using the date of digitization for monographs in a Demand-driven Acquisition (DDA) collection as publication dates. She discusses her experience of a keyword search, explains how a dated content get into a collection, and cites the benefits of spurious metadata for the MARC record generated by an electronic book vendor. Her experience of using an electronic book is also noted.